KRITERIA RUMAH MAKAN SUPPLIER MINYAK JELANTAH DALAM RANGKA PERENCANAAN BAHAN BAKU BIODIESEL - D.U.M. Susilo; Th. Candra Wasis A.S.; Zakwan (Institut Teknologi Sawit Indonesia (ITSI), 2019)
The using of biodiesel as an environmentally friendly fuel has received attention from consumersto producers. So, a lot of research was done on the potential raw material to become biodiesel. One ofthe raw materials for biodiesel was waste cooking oil. Pontianak City have many sources including wastecooking oil from restaurants. Therefore restaurants in the city of Pontianak might be usedas suppliers of waste cooking oil in biodiesel production. This study aims to determine the priority ofcriteria and sub-criteria for restaurants as suppliers and determine good restaurants as suppliers ofused cooking in Pontianak City . Purposive technique sampling using a sample of 61 house dining,interviewed to obtain alternative data suppliers. Expert survey questionnaire contains priority weightingof criteria and supplier criteria, analyzed using AHP ( Analytic Hierarchy Process ). Grouping ofrestaurants based on alternative supplier values is used to determine good restaurants to besuppliers. The priority criteria for restaurants as consecutive suppliers are experience (0.289), quality(0.279), capacity (0.231), service (0.148) and price (0.053). Sub-criteria priority of restaurants assuppliers in a row is the time span of used cooking oil sold(0.161), length of time used cookingoil (0.155), income (0.129), type of cooking oil (0.107), type of fried food products (0.092), volume ofcooking oil (0.090), frying volume (0.085), transaction convenience (0.082), subject to used cooking oil(0.056), used cooking oil price (0.030) and ease of payment (0.013). A value of ≥ 0.325 is a dining valuethat shows a very better priority as a supplier. The number of restaurants as suppliers is 8 % of thepopulation of restaurants in the city of Pontianak.